The effect of exposure to hypoxia on superoxide formation by alveolar macrophages is indirect - Žaloudíková, Marie; Vytášek, Richard; Rašková, Marcela; Vízek, Martin; Uhlík, Jiří; Hampl, Václav (Life sciences, 2019)
AIMS: To elucidate the role of alveolar macrophages (AM) in the pathogenesis of hypoxic pulmonary hypertension (HPH), we tested the effects of sustained hypoxia on AM polarization and on the formation of superoxide by AM in vivo and in vitro. MAIN METHODS: Rat AM were obtained by bronchoalveolar lavage. 4-day exposure to hypoxia (10% O2) was carried out in vivo (rats in isobaric hypoxic chamber, controls kept in air) or in vitro (control AM in 21% O2 and 5% CO2). Superoxide production was measured by luminol-orthovanadate chemiluminescence, AM polarization was detected immunocytochemically. To ascertain the effect of substances contained in the alveolar environment, we cultivated cells also in the presence of non-cellular components of the bronchoalveolar lavage fluid (BALF) either from controls or from rats exposed to 4 days of hypoxia. KEY FINDINGS: In vivo, but not in vitro, hypoxia increased AM superoxide production. Both types of hypoxia polarized AM into M2 (pro-proliferative) type. While the presence of control BALF attenuated superoxide production in AM cultivated in normoxia, BALF from the hypoxia-exposed rats had no effect. In AM cultivated in hypoxia, superoxide production was not altered by control BALF and elevated by BALF obtained from hypoxic rats. SIGNIFICANCE: Hypoxia does not influence superoxide production by AM directly but rather by modulating their milieu and their sensitivity to external influences.
Keywords: superoxidy; Superoxides; Bronchoalveolar Lavage Fluid; krysa rodu Rattus; Hypoxia; zvířata; Cells, Cultured; Chronic hypoxia; potkani Wistar; hypoxie; Superoxide; Macrophage polarization; Rats, Wistar; Male; bronchoalveolární lavážní tekutina; kultivované buňky; Alveolar macrophage; Macrophages, Alveolar; Rats; Animals; mužské pohlaví; alveolární makrofágy